Intercostal Nerve Cryoablation During Lobectomy for Postsurgical Pain: A Safe and Cost-Effective Intervention - Daniel L. Miller; Jacob Hutchins; Michael A. Ferguson; Yazid Barhoush; Emily Achter; John P. Kuckelman (Pain and Therapy)
Abstract Introduction The cost benefit of intercostal nerve cryoablation during surgical lobectomy for postoperative pain management is unknown. The current study compared hospital economics, resource use, and clinical outcomes during the index stay and accompanying short-term follow-up. Patients who underwent lobectomy with standard of care treatment for postsurgical pain management and cryoablation were compared to those with standard of care treatment only. We hypothesized that cryoablation would reduce narcotic use and index hospital and short-term costs. Methods A retrospective, propensity matched cohort of surgical patients treated between 2016 and 2022 from a US National All-Payer Database were used. Cost and outcome comparisons were made between groups using chi-square and t tests. Results From a cohort of 23,138 patients, 266 pairs with a mean age of 69 years were included. Matching variables included age, gender, lobe resected, and prior opioid use. Both groups had significant comorbidity history and prior opioid use; 66% (n = 175 both groups) underwent open lobectomy and 53% (n = 142 vs. 143) had the upper lobe resected. Cryoablation intervention was associated with 1.3 days reduced hospital stay (8.8 vs. 10.1 days, p = 0.31) and no difference in perioperative safety. After 90 days, postsurgery cryoablation patients had lower opioid prescription refills (27.3 vs. 36.9 morphine milligram equivalents, p = 0.03). Cryoablation patient costs trended less than non-cryoablation patients during index ($38,753 vs. $43,974, p = 0.10) and lower through 6 months (total costs, $65,703 vs. $74,304, p = 0.10). There was no difference in postsurgery resource use, but a smaller proportion of cryoablation patients had outpatient hospital visits (83.1%, N = 221 vs. 92.9%, n = 247, p < 0.01). Conclusion Cryoablation during lobectomy is safe and does not add incremental hospital costs. Clinical meaningful reductions in length of stay and postsurgery opioid use were observed with cryoablation intervention. The addition of cryoablation during surgery to reduce postoperative pain appears to be a cost-effective therapy.